A Multi‐sector Model of the Australian Economy1. Issue 298 (26th April 2016) - Rees, Daniel M.; Smith, Penelope; Hall, Jamie
Abstract : This paper describes the dynamic stochastic general equilibrium (DSGE) model currently in use at the Reserve Bank of Australia. The model extends previous DSGE models of the Australian economy by incorporating multiple production sectors, including a resource sector. We estimate the model, describe its dynamic properties, illustrate its use in scenario analysis and use it to identify the sources of Australian business cycle fluctuations.